Annex 1: Terms of reference for the implementation of the project in Latin America - Inter-American Institute for Cooperation on Agriculture (IICA) (2019)
In 2016, IFAD granted CTA a grant to implement the project “Capitalization on Experiences for Greater Impact in Rural Development”, with the specific objective of promoting the sustainable adoption of experience capitalization as an approach for continuous learning, improvement and scaling up in rural development initiatives. The Project proposal was jointly formulated by CTA, IICA and the Food and Agriculture Organization of the United Nations (FAO). While CTA is recipient of the grant and is therefore responsible for the Project implementation, both IICA and FAO agreed to support the implementation of all activities according to working regions.